Temple Construction as a Religious and Political Strategy Srivijaya 7th–12th Century - Hudaidah Hudaidah; Syafruddin Yusuf; Endang Switri; Supiyah Supiyah (Universitas Hamzanwadi, 2026)
The purpose of this study is to analyze the construction of temples during the Sriwijaya era from the 7th to the 12th century as part of a religious strategy related to political interests and the expansion of power. This research is based on the view that temple construction is not only a means of worship but also plays a strategic role in strengthening the kingdom's position. The method used is the historical method with a historical-critical approach. It consists of heuristics, source criticism, interpretation, and historiography. Research findings indicate that temple construction in Srivijaya not only served as centers for religious rituals but also functioned as instruments of political legitimation and as centers of Buddhist education. Thus, the construction of temples was a religio-political strategy that played a role in maintaining internal stability and strengthening Sriwijaya's influence in the Southeast Asian region.